Optimized Whole-Body PET MRI Sequence Workflow in Pediatric Hodgkin Lymphoma Patients - Georgi, Thomas W; Stoevesandt, Dietrich; Kurch, Lars; Bartelt, Jörg M; Hasenclever, Dirk; Dittmann, Helmut; Ferda, Jiri; Francis, Peter; Franzius, Christiane; Furth, Christian; Gräfe, Daniel; Gussew, Alexander; et al. (Journal of nuclear medicine, 2023)
18F-FDG PET/MRI might be the diagnostic method of choice for Hodgkin lymphoma patients, as it combines significant metabolic information from PET with excellent soft-tissue contrast from MRI and avoids radiation exposure from CT. However, a major issue is longer examination times than for PET/CT, especially for younger children needing anesthesia. Thus, a targeted selection of suitable whole-body MRI sequences is important to optimize the PET/MRI workflow. Methods: The initial PET/MRI scans of 84 EuroNet-PHL-C2 study patients from 13 international PET centers were evaluated. In each available MRI sequence, 5 PET-positive lymph nodes were assessed. If extranodal involvement occurred, 2 splenic lesions, 2 skeletal lesions, and 2 lung lesions were also assessed. A detection rate was calculated dividing the number of visible, anatomically assignable, and measurable lesions in the respective MRI sequence by the total number of lesions. Results: Relaxation time-weighted (T2w) transverse sequences with fat saturation (fs) yielded the best result, with detection rates of 95% for nodal lesions, 62% for splenic lesions, 94% for skeletal lesions, and 83% for lung lesions, followed by T2w transverse sequences without fs (86%, 49%, 16%, and 59%, respectively) and longitudinal relaxation time-weighted contrast-enhanced transverse sequences with fs (74%, 35%, 57%, and 55%, respectively). Conclusion: T2w transverse sequences with fs yielded the highest detection rates and are well suited for accurate whole-body PET/MRI in lymphoma patients. There is no evidence to recommend the use of contrast agents.
Keywords: nemoci kostí; Positron-Emission Tomography; Radiopharmaceuticals; fluorodeoxyglukosa F18; radiofarmaka; whole-body imaging; Hodgkin Disease; Hodgkin lymphoma; Diffusion Magnetic Resonance Imaging; Fluorodeoxyglucose F18; dítě; Child; difuzní magnetická rezonance; magnetická rezonanční tomografie; Positron Emission Tomography Computed Tomography; Neoplasm Staging; Magnetic Resonance Imaging; Humans; Whole Body Imaging; pozitronová emisní tomografie; PET/CT; PET/MRI; MRI sequences; Hodgkinova nemoc; staging nádorů; Bone Diseases; celotělové zobrazování; lidé; Workflow; průběh práce